The interactome of stabilized α‐synuclein oligomers and neuronal proteins. (24th November 2019) - van Diggelen, Femke; Frank, Signe Andrea; Somavarapu, Arun Kumar; Scavenius, Carsten; Apetri, Mihaela M.; Nielsen, Janni; Tepper, Armand W. J. W.; Enghild, Jan J.; Otzen, Daniel E.
Abstract : While it is generally accepted that α‐synuclein oligomers (αSOs) play an important role in neurodegeneration in Parkinson's disease, the basis for their cytotoxicity remains unclear. We have previously shown that docosahexaenoic acid (DHA) stabilizes αSOs against dissociation without compromising their ability to colocalize with glutamatergic synapses of primary hippocampal neurons, suggesting that they bind to synaptic proteins. Here, we develop a proteomic screen for putative αSO binding partners in rat primary neurons using DHA‐stabilized human αSOs as a bait protein. The protocol involved co‐immunoprecipitation in combination with a photoactivatable heterobifunctional sulfo‐LC‐SDA crosslinker which did not compromise neuronal binding and preserved the interaction between the αSOs‐binding partners. We identify in total 29 proteins associated with DHA‐αSO of which eleven are membrane proteins, including synaptobrevin‐2B (VAMP‐2B), the sodium–potassium pump (Na + /K + ATPase), the V‐type ATPase, the voltage‐dependent anion channel and calcium‐/calmodulin‐dependent protein kinase type II subunit gamma; only these five hits were also found in previous studies which used unmodified αSOs as bait. We also identified Rab‐3A as a target with likely disease relevance. Three out of four selected hits were subsequently validated with dot‐blot binding assays. In addition, likely binding sites on these ligands were identified by computational analysis, highlighting a diversity of possible interactions between αSOs and target proteins. These results constitute an important step in the search for disease‐modifying treatments targeting toxic αSOs. Abstract : Oligomers of the protein α‐synuclein (αSOs) are central in the development of Parkinson's disease and thus important therapeutic targets. We use chemical crosslinking and proteomics to identify protein binding partners for these αSOs in their likely physiological habitat, namely intact primary neurons. Out of 32 hits, more than one‐third are membrane proteins. We validate hits and identify possibly oligomer‐binding sites by computational analysis.